An Evaluation of IFC’s Investment Climate Activities - Operations Evaluation Group (International Finance Corporation, Washington, D.C., 2017)
This report is part of a joint Operations Evaluation Department (OED) and Operations Evaluation Group (OEG) and Operations Evaluation Unit (OEU) evaluation of World Bank Group (WBG) investment climate activities based on an approach paper issued to the Board Committee on Development Effectiveness (CODE) in November 2002, to help inform pursuit of the WBG’s private sector development (PSD) strategy. The objective of the OEG review is to inform International Finance Corporation’s (IFC’s) strategy for addressing investment climate (IC). IFC has been increasing its IC activities, mostly through non-investment operations, and yet no evaluation has been done to date to take stock of the overall IFC IC experience from FY93-02 and lessons learned. Similarly, the WB has been increasingly active in IC operations both unilaterally and bilaterally with IFC. The study also aims to draw lessons from the WB, IFC, and Multilateral Investment Guarantee Agency (MIGA) coordination on IC activities. For more publications on IFC Sustainability please visit www.ifc.org/sustainabilitypublications.